Phenotypic divergence and biometric indices of silond catfish, Silonia silondia (Hamilton 1822) populations inhabiting the coastal rivers of Bangladesh. Issue 12 (December 2022) - Ullah, Md. Rahamat; Rahman, Md. Arifur; Siddik, Muhammad A.B.; Alam, Md. Ariful
Abstract: To observe phenotypic differentiation among populations of Silond catfish, Silonia silondia (Hamilton 1822), a multilinear approach was used. A sum of 180 samples from three coastal rivers (Meghna, Payra, and Kirtankhola) of the Bangladesh coast were scooped up to comprehend whether distinct populations of S. silondia could be separated from one another due to adaptive divergence. The findings of this study reflect the first attempt to determine the stock structure, morphological characters, length-frequency distributions, length-length relationships, length-weight relationships, condition factors, relative weight, and form factor of S. silondia in the coastal rivers of Bangladesh. Important discrepancies between the means of the three populations were revealed using univariate and multivariate analysis of variance ( p < 0.01). In principal component analysis, the first and second principal components described 83.546% and 4.302% of the total variation, respectively. The step-wise discriminant function analysis revealed two variables that separated the populations significantly. Besides, a dendrogram based on Euclidean distances accurately separated the populations. In a one-way analysis of variance study, nineteen out of twenty-one morphometric characters showed significant variation ( p < 0.01)among three populations. The length parameters based on the length-length relationships of each sample were found to be highly significant ( p < 0.01). The length-weight relationships exhibited that the b value fluctuated from 2.796 (Kirtankhola) to 3.498 (Meghna). The Fulton's condition factor was estimated in the current study for this species with an average value ranging from 1.12 to 1.35. The calculated form factor values of this species were 0.0016, 0.0054, and 0.0110 for Meghna, Payra, and Kirtankhola river, respectively. Therefore, this study will expectantly inform fisheries taxonomists about the species' current stock structure, intraspecific phenotypic divergences, and aid in its management and conservation in similar ecosystems in Bangladesh and around the world. Abstract : Biometric indices; Coastal rivers; Phenotypic divergence; Silond catfish.